Predators as drivers of insect defenses. Issue 3 (25th June 2020) - Sugiura, Shinji
Abstract: Insects have evolved various types of antipredator defenses. For example, many insects have evolved crypsis, and exhibit cryptic body colors and shapes for hiding from predators. Other insects produce toxins as a form of chemical defense against predators, and some toxic insects are aposematic, with conspicuous body colors for advertising their toxins. Insects can also develop hairs, spines or hard exoskeletons as morphological defenses to protect themselves from predation. In addition, insects can evolve behavioral defenses, in which insects exhibit autotomy or dropping, or feign death. This study investigated which predator types evoke these types of defenses, through a review of the effectiveness of antipredator defenses in insects against carnivorous animals that are commonly used as model predators in studies. These predators include other insects, spiders, fish, frogs, lizards, birds and mammals. The results provide the first step for clarifying the evolutionary drivers of antipredator defenses in insects. The following aspects should be considered for future studies: multiple predator species and sufficient replication, alternative prey and predator models, and tolerance to predators in insects. Abstract : Insects have evolved various types of anti‐predator defenses. This study investigated which predator types evoke defenses, through a review of the effectiveness of anti‐predator defenses in insects against carnivorous animals that are commonly used as model predators in studies. The results provide the first step for clarifying the evolutionary drivers of anti‐predator defenses in insects.